Reactive Oxygen Species Function to Mediate the Fe Deficiency Response in an Fe-Efficient Apple Genotype: An Early Response Mechanism for Enhancing Reactive Oxygen Production - Sun, Chaohua; Wu, Ting; Zhai, Longmei; Li, Duyue; Zhang, Xinzhong; Xu, Xuefeng; Ma, Huiqin; Wang, Yi; Han, Zhenhai (Frontiers in Plant Science, 2016)
Abstract Reactive oxygen species (ROS) are important signaling molecules in plants that contribute to stress adaption. This study demonstrated that ROS play a critical role in Fe deficiency-induced signaling at an early stage in Malus xiaojinensis. Once ROS production has been initiated, prolonged Fe starvation leads to activation of ROS scavenging mechanisms. Further, we demonstrated that ROS scavengers are involved in maintaining the cellular redox homeostasis during prolonged Fe deficiency treatment. Taken together, our results describe a feedback repression loop for ROS to preserve redox homeostasis and maintain a continuous Fe deficiency response in the Fe-efficient woody plant M. xiaojinensis. More broadly, this study reveals a new mechanism in which ROS mediate both positive and negative regulation of plant responses to Fe deficiency stress.